2020
DOI: 10.1103/physrevd.102.054020
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic corrections to the vector meson light front wave function

Abstract: We compute a light front wave function for heavy vector mesons based on long-distance matrix elements constrained by decay width analyses in the nonrelativistic QCD framework. Our approach provides a systematic expansion of the wave function in quark velocity. The first relativistic correction included in our calculation is found to be significant and crucial for a good description of the HERA exclusive J=ψ production data. When looking at cross section ratios between nuclear and proton targets, the wave funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 115 publications
(192 reference statements)
2
56
0
Order By: Relevance
“…The virtual photon wave functions describing the γ * → quark-antiquark splitting can be further employed to investigate the exclusive vector meson production in virtual photon-proton (or nucleus) scattering. [52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The virtual photon wave functions describing the γ * → quark-antiquark splitting can be further employed to investigate the exclusive vector meson production in virtual photon-proton (or nucleus) scattering. [52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, we only need to compute the leading order corrections of C 0 q q q q and the leading order contribution to C 0 q qg q q. A study of finite k corrections can be found in [5].…”
Section: Quarkonium Light Cone Wave Function In the Non-relativistic Limitmentioning
confidence: 99%
“…Different parametrizations for these objects have been recently compared when studying rapidity distributions [96] where the authors find large systematics uncertainties. Recent developments on relativistic corrections to vector meson light-cone wave-functions can be found in [97].…”
Section: Competing Mechanisms and Systematic Uncertaintiesmentioning
confidence: 99%